Substantiation of disciplinary summaries of public servants of the Decentralized Autonomous Governments by the Ministry of Labor - Montesdeoca Macías, Robert; Mieles Velásquez, Carlos; Reyna Zambrano, María Yokir (Frónesis, 2023)
Analyzing the competence for the substantiation of disciplinary summaries of public servants of the Decentralized Autonomous Governments of Ecuador of the Ministry of Labor against the principle of autonomy of the first of those named, is the general objective of the bibliographic review article. The relevance of the study is to reveal, in accordance with legislation and specialized doctrine, whether this power is compatible with the postulates of the modern constitutional State, rights and justice. The thematic axis of this analysis is the disciplinary sanctioning power and the principle of autonomy, legal institutions that, despite having a vast bibliography, do not particularly address this problem, which arises from Ministerial Agreement No. MDT-2017- 0169-0169, which establishes the actions of the Ministry of Labor in this field. The results allow us to consider that disciplinary power is subject to clear norms and rules as a reflection of the progress experienced in Ecuador since the promulgation of the Constitution of the Republic. It is concluded that the normative act issued that reforms the Organic Law of the Public Service and delegates the substantiation of the administrative summaries to the Ministry of Labor, contradicts the constitutional legal order, negatively impacting the principle of autonomy of the Decentralized Autonomous Governments.